Wishart random matrix based Bayesian estimation for time-varying channel in the color noise - JING Yuan; YIN Fu-liang (Tongxin xuebao)
A Bayesian estimation method for time-varying channel with the color noise was proposed.Based on random matrix theory and Gibbs sampling,the covariance matrix of the color noise and the channel parameters were firstly esti-mated.Then,the proposal distribution（or importance distribution） of the sequential monte carlo（SMC） sampler was modified to track the time-varying channel parameters blindly（with no pilot signals）.Therefore,the proposed method may online semi-blindly estimate the time-varying channel parameters in the background of color noise.Compared with existing approaches,which are based on Kalman filtering and particle filtering,the proposed method is more robust and more accurate while the color noise is considered.The simulation results show the effectiveness of the proposed method.